Comparing musical ambiguity in Hafiz's poem with two same-style previous poets; Khajou and Amir Khosro - saeed ghaseminia; esmat esmaeili (مطالعات زبانی و بلاغی)
One obvious feature of Hafiz's style is ambiguity and among this, ambiguity of musical words has obvious usage. Among the poets that hafiz was under the influence of them; Khajou kermani and Amir Khosro dehlavi clearly use musical ambiguity too. so that some of words that make ambiguity in their poems have been used with common structures . Our main question is that in use of ambiguity, to what extent hafiz was impressed by Khajou and Amir Khosro. For this purpose, first we have extracted musical ambiguity of the three Divan, then we have separated mutual ambiguities and have written brief description of semantic and structural features of each of them, and by doing so, we have demonstrated that hafiz in his feature style, has paid special attention to khajou's poetry and Amir Khosro's Poetry.